THE DEVELOPMENT OF A GUIDELINE FOR PARTICIPATION IN OCCUPATION TRAINING IN MECHANICS DEPARTMENT BETWEEN COLLEGES AND ESTABLISHMENTS UNDER KALASIN VOCATIONAL EDUCATION - Phuhadkarn, Maitree; Julsuwan, Suwat (Journal of MCU Nakhondhat, 2020)
This study aimed 1) to investigate the current situations, desired situations and needs of participation 2) to develop guidelines for participation of occupation training in mechanics department between colleges and establishments under Kalasin vocational Education. The Population 392 were sample of investigating related to the current situations, desired situations and needs of participation was 118 consisted of college administrators. The instruments used in the study consisted of 5 rating scales questionnaire, structured interview and the suitability and possibility evaluation form. The results revealed that: 1) All aspects of the current situations of participation for occupation training in mechanics department between colleges and establishments under Kalasin vocational Education were shown in more level ( = 3.62) and all aspects of the desired situations were ranged in the most level ( = 4.55). The index of needs revealed as follows; the participation of evaluation, decision making participation, planning participation and problems awareness participation. 2) The guidelines for occupation training in mechanics department between colleges and establishments pointed that the stability was in the most level ( = 4.14) and the possibility was also in the most level ( = 4.59). The vital issues of guideline development were shown as follows; invitation the speaker to give a special training to students before internship, the participation of making rules in occupation training, the participation of making evaluation details of occupation training, the participation of ethics and moral evaluation, the participation of curriculum compiling, the participation of occupation training supervision, the participation of behavior problem awareness and dealing with the problems of students, the participation of evaluation and assessment and the participation of raising awareness of the image and prominent of the colleges and the establishments.